Hypomagnesaemia and Relationship Lipid Profile in Type 2 Diabetes Patients at Janzur Hospital in Libya. - Ashraf Alapid; Apoajela Ahmed; Mohammed Wana; Moudah Shadi (AlQalam Journal of Medical and Applied Sciences, 2024)
Type 2 diabetes mellitus (T2DM) is associated with increased morbidity and mortality due to the development of complications, especially due to poor glycemic control. Magnesium (Mg) is a crucial element in human health, and its deficiency plays a critical role in the development of lipid abnormalities and the initiation of diabetic complications. The study aimed to evaluate the correlation of hypomagnesemia (Mg) with the alteration of lipid profile patterns and investigate the adverse effects of glycemic control and body mass index (BMI) on magnesium levels among patients with T2DM. A total of 163 subjects whose ages ranged between 35-60 years for both sexes (males and females) were included in this study: 90 type II diabetic patients (40 males and 50 females) and 73 healthy individuals (34 males and 39 females) in Tripoli region, Western Libya. Blood glucose, HbA1c, Magnesium, and lipid profile parameters were biochemically estimated in the study along with the measurement of BMI. All the results were statistically analyzed using SPSS version 25 for applying one-way ANOVA and Person’s correlation coefficient tests. The study revealed a significant decrease in serum magnesium levels (1.59 ± 0.47 mg/dL) in T2DM patients compared to the control group (2.21 ± 0.70 mg/dL) (p < 0.01). Significantly elevated levels of blood glucose (140.6 ± 30.95 mg/dL vs. 89.80 ± 12.62 mg/dL, p < 0.01), HbA1c (7.27 ± 2.62% vs. 5.32 ± 0.65%, p < 0.01), cholesterol, triglycerides and LDL cholesterol also observed in T2DM patients compared to healthy individuals. Conversely, HDL cholesterol levels were significantly lower in the T2DM group than in controls (24.44 ± 8.88 mg/dL vs. 47.06 ± 8.75 mg/dL, p < 0.01). There is a relationship between hypomagnesemia, glycemic control, and changed lipid profile in T2DM patients. Further, our results revealed a strong relationship between increased BMI and unfavorable alterations in all biochemical parameters examined. يرتبط مرض السكري من النوع الثاني بزيادة معدلات الإصابة والوفيات بسبب تطور المضاعفات، وخاصة بسبب ضعف التحكم في نسبة السكر في الدم. يعد المغنيسيوم عنصرًا حاسمًا في صحة الإنسان، ويلعب نقصه دورًا حاسمًا في تطور اضطرابات الدهون وبدء المضاعفات السكرية. هدفت الدراسة إلى تقييم ارتباط نقص المغنيسيوم في الدم بتغيير أنماط الدهون والتحقيق في الآثار الضارة للتحكم في نسبة السكر في الدم ومؤشر كتلة الجسم على مستويات المغنيسيوم بين مرضى السكري من النوع الثاني. تم تضمين ما مجموعه 163 شخصًا تتراوح أعمارهم بين 35-60 عامًا لكلا الجنسين (ذكور وإناث) في هذه الدراسة: 90 مريضًا مصابًا بمرض السكري من النوع الثاني (40 ذكرًا و50 أنثى) و73 فردًا سليمًا (34 ذكرًا و39 أنثى) في منطقة طرابلس، غرب ليبيا. تم تقدير مستويات الجلوكوز في الدم، والهيموجلوبين السكري، والمغنيسيوم، ومستويات الدهون كيميائيًا في الدراسة جنبًا إلى جنب مع قياس مؤشر كتلة الجسم. تم تحليل جميع النتائج إحصائيًا باستخدام برنامج SPSS الإصدار 25 لتطبيق اختبارات تحليل التباين أحادي الاتجاه ومعامل ارتباط بيرسون. كشفت الدراسة عن انخفاض كبير في مستويات المغنيسيوم في المصل (1.59 ± 0.47 مجم / ديسيلتر) في مرضى السكري من النوع 2 مقارنة بمجموعة التحكم (2.21 ± 0.70 مجم / ديسيلتر). كما لوحظت مستويات مرتفعة بشكل ملحوظ من جلوكوز الدم (140.6 ± 30.95 مجم / ديسيلتر مقابل 89.80 ± 12.62 مجم / ديسيلتر، ص < 0.01)، والهيموجلوبين السكري (7.27 ± 2.62٪ مقابل 5.32 ± 0.65٪، ص < 0.01)، والكوليسترول، والدهون الثلاثية وكوليسترول البروتين الدهني منخفض الكثافة في مرضى السكري من النوع 2 مقارنة بالأفراد الأصحاء. وعلى العكس من ذلك، كانت مستويات الكوليسترول الحميد أقل بشكل ملحوظ في مجموعة السكري من النوع 2 مقارنة بمجموعة التحكم (24.44 ± 8.88 مجم / ديسيلتر مقابل 47.06 ± 8.75 مجم / ديسيلتر، ص < 0.01). هناك علاقة بين نقص المغنيسيوم، والسيطرة على نسبة السكر في الدم، وتغير انماط الدهون في مرضى السكري من النوع 2. علاوة على ذلك، كشفت نتائجنا عن وجود علاقة قوية بين زيادة مؤشر كتلة الجسم والتغيرات السلبية في جميع المعايير الكيميائية الحيوية التي تم فحصها